2015
DOI: 10.1155/2015/318269
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Surgery Combined with Autologous Bone Marrow Stromal Cell Transplantation for Treatment of Intracerebral Hemorrhage

Abstract: Bone marrow stromal cells (BMSCs) may differentiate into nerve cells under a certain condition; however, the clinical application for treating nervous system disease remains unclear. The aim is to assess the safety profile, feasibility, and effectiveness of surgery combined with autologous BMSCs transplantation for treating ICH. 206 ICH patients who had received surgical procedure were divided into transplantation (n = 110) or control group (n = 96). For transplantation group, BMSCs were injected into the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…The majority of studies (n=18) utilised autologous adult human bone marrow-derived mesenchymal/mononuclear cells [ 13 , 16 22 , 24 - 26 , 30 – 34 , 36 , 37 , 39 ]. The remaining studies utilised varied allogeneic cell sources such as human neural stem cells derived from fetal tissue (n=3) [ 15 , 29 , 38 ], mesenchymal cells from umbilical cord blood (n=1) [ 23 ], neuronal cells derived from embryonic tissue ( n = 2) [ 12 , 14 ] and autologous peripheral blood haematopoietic stem cells ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies (n=18) utilised autologous adult human bone marrow-derived mesenchymal/mononuclear cells [ 13 , 16 22 , 24 - 26 , 30 – 34 , 36 , 37 , 39 ]. The remaining studies utilised varied allogeneic cell sources such as human neural stem cells derived from fetal tissue (n=3) [ 15 , 29 , 38 ], mesenchymal cells from umbilical cord blood (n=1) [ 23 ], neuronal cells derived from embryonic tissue ( n = 2) [ 12 , 14 ] and autologous peripheral blood haematopoietic stem cells ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Zhu and collaborators [ 78 ] carried out a clinical trial where 215 patients with ICH were included. Following surgical drainage and decompressive craniotomy, 114 patients agreed to receive the cell therapy while the remaining 101 patients participated as a control group.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Zhu et al compared outcomes of surgery combined with autologous bone marrow stromal cell transplantation vs. surgery alone for treatment of intra-cerebral hemorrhage. The findings of this trial showed that surgery combined with autologous bone marrow stromal cell transplantation is safe, providing short-term therapeutic benefits for ICH (36).…”
Section: Discussionmentioning
confidence: 90%